Liposomes-Based Drug Delivery Systems of Anti-Biofilm Agents to Combat Bacterial Biofilm Formation - Zinb Makhlouf; Amaal Abdulraqeb Ali; Mohammad Hussein Al-Sayah (MDPI AG, 2023)
All currently approved antibiotics are being met by some degree of resistance by the bacteria they target. Biofilm formation is one of the crucial enablers of bacterial resistance, making it an important bacterial process to target for overcoming antibiotic resistance. Accordingly, several drug delivery systems that target biofilm formation have been developed. One of these systems is based on lipid-based nanocarriers (liposomes), which have shown strong efficacy against biofilms of bacterial pathogens. Liposomes come in various types, namely conventional (charged or neutral), stimuli-responsive, deformable, targeted, and stealth. This paper reviews studies employing liposomal formulations against biofilms of medically salient gram-negative and gram-positive bacterial species reported recently. When it comes to gram-negative species, liposomal formulations of various types were reported to be efficacious against Pseudomonas aeruginosa, Escherichia coli, Acinetobacter baumannii, and members of the genera Klebsiella, Salmonella, Aeromonas, Serratia, Porphyromonas, and Prevotella. A range of liposomal formulations were also effective against gram-positive biofilms, including mostly biofilms of Staphylococcal strains, namely Staphylococcus aureus, Staphylococcus epidermidis, and Staphylococcus saprophyticus subspecies bovis, followed by Streptococcal strains (pneumonia, oralis, and mutans), Cutibacterium acnes, Bacillus subtilis, Mycobacterium avium, Mycobacterium avium subsp. hominissuis, Mycobacterium abscessus, and Listeria monocytogenes biofilms. This review outlines the benefits and limitations of using liposomal formulations as means to combat different multidrug-resistant bacteria, urging the investigation of the effects of bacterial gram-stain on liposomal efficiency and the inclusion of pathogenic bacterial strains previously unstudied.